ADVANCES IN SCIENCE IN GREAT BRITAIN - Norqobilov Boburjon; Botirova Hakima (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Great Britain has long been at the forefront of scientific research and discovery, making significant contributions to various fields of study. From groundbreaking inventions to pioneering discoveries, British scientists have reshaped our understanding of the world, revolutionizing industries and improving countless lives. In this article, we will explore some of the notable advances in science that have emerged from the United Kingdom.